Soft tissue tumours of the penis. The 30-year Istituto Nazionale Tumori di Milano experience - Colecchia, Maurizio; Pini , Giacomo Maria; Pruneri, Giancarlo; Nicolai, Nicola; Servillo, Sascia (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2024)
Objective. Small series and individual cases of penile soft tissue tumours are reported in the literature: these are rare tumours that represent less than 5% of all penile tumours.Methods. Penile soft tissue tumours were collected from the archive of the Department of Pathology at the Istituto Nazionale dei Tumori of Milan between January 1990 and October 2021. All available medical records were retrieved and reviewed to obtain clinical information.Results. Our series refers to the 30-year experience of highlighting the heterogeneity in the presentation and microscopic features of these rare sarcomas. 18 penile soft tissue tumours are described, 4 benign and 14 malignant. The mean age at diagnosis was 58.2 years (range 24-96 years) and 53.6 years among malignancies (range 24-89). The most frequent histotype was Kaposi’s sarcoma (nr = 4) and very unusual histotypes were observed, namely low-grade fibromyxoid sarcoma, synovial sarcoma, proximal type epithelioid sarcoma and the first reported case of dedifferentiated liposarcoma of the penis.Conclusions. Among sarcomas of the genitourinary tract, tumours of the soft tissues of the penis are the rarest. Penile sarcomas can present at a young age. Kaposi’s sarcoma in HIV-negative patients has a favorable outcome, while deep sarcomas have an aggressive behavior and poor prognosis.